Análise das características elétricas das matrizes compósitas (1–x)ZnZrNb2O8 ‒ (x)CaTiO3 para aplicações em componentes de radiofrequência e micro-ondas - Holanda, Lucas Freire de (2022)
The present work describes the development of new ceramic materials based on ZnZrNb2O8 (ZZNO). The addition of CaTiO3 (CTO) in different proportions was performed to synthesize the composites, with general formula (1–x)ZnZrNb2O8-(x)CaTiO3 (0 ≤ x ≤ 0.40, mass fraction). The ZZNO phase was prepared by solid state reaction method. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were carried out to evaluate the structural and morphological characteristics, respectively. Impedance spectroscopy (IS) was used for the dielectric characterization in the radiofrequency region and the Hakki-Coleman and Silva-Fernandes-Sombra methods were used to evaluate the properties in the microwave region. The XRD results showed that the ZZNO phase with monoclinic structure was successfully obtained and that there was the formation of different secondary phases in the composites formed by the addition of CTO to ZZNO. The IS analysis provides the first results for the characterization of ZZNO in radiofrequency, with permittivity (ε’) = 28.6 at 40 ºC and loss tangent (tg δ) = 2.6×10‒3 at 1 MHz and 40 º C. The ε’ values were between 4.1 and 1.65×10‒3 and tg δ values between 2.0×10‒3 and 23.29 were obtained for the composites with CTO. The analysis of Nyquist plots for all samples indicated a non-Debye type behavior and an equivalent circuit was proposed to evaluate the electric effects of grain and grain boundaries. Thermal stability was evaluated from the calculation of the temperature coefficient of capacitance (TCC) and the ZZNO and the samples with 10% of CTO (x = 0.10) exhibited high thermal stability in the region of 1 MHz. The dielectric microwave properties were investigated, and the values of εr were between 23.45 and 53.89 and tg δ values were between 2.07×10–4 and 1.06×10–2. The temperature coefficient of resonant frequency (τf) values ranged between –51.50 and +38.47 ppm ºC–1. The composites with 13% (x = 0.13), with τf = –2.09 ppm ºC–1, and 14% of CTO (x = 0.14), with τf = +2.05 ppm ºC–1, were the ones that showed the highest thermal stability in the microwave region. Numerical simulation was also performed to evaluate the behavior of the ceramics as dielectric resonator antenna and the samples presented gain from 3.64 to 5.32 dBi, bandwidth ranging between 56.40 and 130.17 MHz and efficiency between 72.00 and 99.10%, indicating the great potential of application in microwave region.